¿Guerrilla Christ or Christ the king? The theology of violence in Cristianismo y Revolución (1969-1971) - Campos, Esteban (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2013)
The problem of this research is the organisation of the theological discourse in recent issues of Christianity and Revolution (C Y R, and up), taking into account the evolution of doctrinal content articles and specific socio-historical context. In sections of the magazine that addressed the question of religion, it can be noted the passage of refreshing Catholicism to the liberationist Christianity. Following the same number of matches, there is a shift of the new conciliar theology to the theology of violence, directly involved in the political debate. To prove this working hypothesis we observe the column "Theology", analyzing the relationship between violence, ends and means in the articles of Jalles Costa, Olivier Maillard, Jurgen Moltmann, Ruben Dri, Hernán Benítez and José María González Ruiz. The methodology combines the contributions of sociology and political theory with evidence collection by the techniques of oral history.